DEVELOPING INTERACTIVE LEARNING MULTIMEDIA TO TEACH READING NARATIVE TEXT BY USING ARTICULATE STORYLINE 3 - Riyadi, Maskur; Rosnija, Eni; Salam, Urai (Universitas Tanjungpura, 2024)
The aim of this research was to find out the appropriate design of the reading interactive learning multimedia for the Eight grades student of SMPN 04 Batu Ampar. The type of this research was Research and Development (RD). The procedure was adapted from ADDIE model by Taylor. ADDIE stands for analyse, Design, Develop, Implementation, and Evaluate. The subject of this research was the eight grades students of SMPN 04 Batu Ampar. The data were collected through questionaries (need analysis and Expert Judgment). Design phase was done to prepare the appropriate material to create the application. Develop phase was done to create an essential part of the N4V (Narrative text for Vocabulary). The design product was complete after have an expert validation regarding to the student needs, and already stated valid to be use by the expert validator. The N4V considering the Learning Multimedia, Application and Games. To sump up, it was found that N4V is usable to support learning reading narrative text to assist students in enrich vocabulary.